Gender Deformity in Vijay Tendulkar’s Kamala and Kanyadaan: Unveiling Gender Inequality in Tendulkar's Plays (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Vijay Tendulkar was a leading contemporary Indian playwright, movie and televisionwriter, literary essayist and political journalist. He started his career as a journalist in ‘Marathi Weekly’ he wrote all his plays in his native language ‘Marathi’. But most of his plays have been translated and performed in many Indian languages. English versions of his works are more popular than that of other language versions. During his life time, he produced twenty-eight full length plays and twenty-four one act plays, articles, editorials and eleven plays for children. He was also the author of original stories and screen plays for eight films like Akrosh, Gahrayi, Manthan, Nishant, Kamala, Musafir, Ardhasatya and Umbartha. The aim of this paper is to show how women in society are victimized, oppressed, suffered, tortured and exploited and how gender deformity plays an important role in his famous plays Kamala and Kanyadan.